SANKSI ADAT TERHADAP PERKAWINAN SESAMA ANAK TIRI DI NAGARI CANDUANG KOTO LAWEH KABUPATEN AGAM SUMATERA BARAT - Ory Kartika; Zulfikar Jaya Kusuma; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Marriage is an inner bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family or household based on the Godhead. Not all marriages can be held even though the marriage has met the harmonious terms and conditions specified. Just as the marriage that took place in Nagari Canduang Koto Laweh is done by a fellow stepchild or stepbrother where the marriage is prohibited by the customs prevailing in Nagari Canduang Koto Laweh.Some of the issues that will be discussed in this thesis are: First, how the Minangkabau customary law regulates the marriage of stepchildren and the development of marital institutions. Second, how are the traditional sanctions on the marriage of fellow stepchildren in Nagari Canduang Koto Laweh, Agam Regency, West Sumatra. The type of research used is sociological research in the form of research on legal identification (unwritten law).Based on the results of this study it can be concluded that: First, the Minangkabau customary law which applies in the Canduang Koto Laweh village does not allow the marriage of fellow stepchildren because it has not happened before and is usually done by the people in Canduang nagari. Secondly, Niniak Mamak and the local community provide some sanctions to those who carry out the marriage because they have violated the prevailing customs.The advice that can be given is that in the future there will be no more traditional violations such as the marriage of fellow stepchildren or marriages made with stepbrothers in Nagari Canduang Koto Laweh so that the customs in Nagari Canduang remain upheld by the people in Nagari Canduang and sanctions are given explicitly to those who violate adat so that they are not imitated by other communities.Keywords: Customary Sanctions, Stepchild Marriage, Nagari Canduang Koto Laweh